2016
DOI: 10.1007/s10198-016-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

A method to simulate incentives for cost containment under various cost sharing designs: an application to a first-euro deductible and a doughnut hole

Abstract: Many health insurance schemes include deductibles to provide consumers with cost containment incentives (CCI) and to counteract moral hazard. Policymakers are faced with choices on the implementation of a specific cost sharing design. One of the guiding principles in this decision process could be which design leads to the strongest CCI. Despite the vast amount of literature on the effects of cost sharing, the relative effects of specific cost sharing designs—e.g., a traditional deductible versus a doughnut ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The studies included in this theme investigated consequences such as the utilization of health services, health costs, health related behavior, the choice of insurance plan, and the opinion and acceptance of consumers using quantitative, qualitative, review, and theoretical approaches (model-based), the results of quantitative studies are reported in narrative form as follows: modest to high reduction in health services and medications utilization [ 9 , 20 , 21 , 23 , 33 , 38 , 44 , 45 , 47 , 49 , 51 , 55 , 56 , 64 , 69 , 71 ], reduction in health cost [ 21 , 39 , 41 , 42 , 44 , 53 , 65 , 68 ], low or no significant effect on health services utilization [ 6 , 34 , 35 , 40 , 62 , 63 , 65 ], low or no significant effect on health costs [ 5 ], increasing cost contaminate incentive (CCI) [ 57 ], significant correlation with higher preventive behavior [ 13 , 50 ] modest efficiency gain [ 18 ], increasing medication adherence [ 48 ], increasing demand for low price drug [ 61 ], optimal insurance [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included in this theme investigated consequences such as the utilization of health services, health costs, health related behavior, the choice of insurance plan, and the opinion and acceptance of consumers using quantitative, qualitative, review, and theoretical approaches (model-based), the results of quantitative studies are reported in narrative form as follows: modest to high reduction in health services and medications utilization [ 9 , 20 , 21 , 23 , 33 , 38 , 44 , 45 , 47 , 49 , 51 , 55 , 56 , 64 , 69 , 71 ], reduction in health cost [ 21 , 39 , 41 , 42 , 44 , 53 , 65 , 68 ], low or no significant effect on health services utilization [ 6 , 34 , 35 , 40 , 62 , 63 , 65 ], low or no significant effect on health costs [ 5 ], increasing cost contaminate incentive (CCI) [ 57 ], significant correlation with higher preventive behavior [ 13 , 50 ] modest efficiency gain [ 18 ], increasing medication adherence [ 48 ], increasing demand for low price drug [ 61 ], optimal insurance [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 , 6 , 9 , 10 , 13 , 15 , 18 – 20 , 22 – 25 , 27 – 33 , 35 49 , 51 57 , 59 67 , 70 73 , 78 ]…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In section 6 we show that the average deductible elasticity in our model here is the same. Van Kleef et al (2009) and Cattel et al (2017) already show the shifted deductible's potential for reducing moral hazard in the Netherlands. In this paper, we build on this by quantifying how much a shifted deductible can reduce healthcare expenditures and, in fact, out-of-pocket payments.…”
Section: Introductionmentioning
confidence: 99%
“…Among the above methods, one of the ways that have been taken into consideration in recent years in some of the world developed countries is paying deductibles. In this method, the insured person must pay a certain and fixed amount for covered health care services before the insurance organization starts to pay ( 4 ). The philosophy of deductibles is that most insured persons can afford low expenses of visits, medications, etc.…”
Section: Introductionmentioning
confidence: 99%